Policy Rules and Political Polarization - Carsten Hefeker; Michael Neugart (Center for Economic Studies and ifo Institute (CESifo), 2024)
We develop a model to analyze policymakers' incentives to install policy rules, comparing the case of no rule with a binding and a contingent policy rule that allows policymakers to suspend the rule in response to a sufficiently large shock. First, abstracting from political polarization, we show that the choice of the policy rule depends on policymakers' policy targets. Depending on the policy target, there is an unambiguous ranking going from a no-rule regime to a contingent rule to a binding rule. Next, allowing for political polarization, the incentive to install the different types of rules changes with political polarization between different policymakers and their probability of being elected into office. Increasing political polarization when there is a sufficiently high election probability for policymakers with a high policy target increases the preference for more binding policy rules. It also leads to stricter rules in a contingent rule regime.
Keywords: D78; E60; 330; contingent policy rules; political polarization; time inconsistency; electoral uncertainty